2015
DOI: 10.18203/issn.2454-2156.intjscirep20151498
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of knee MRI prescriptions in a hospital of Birjand, 2014

Abstract: <p class="abstract"><strong>Background:</strong> Knee pain is one of the most common complains which cause patients to visit a doctor and Magnetic Resonance Imaging (MRI) is one of the common diagnostic methods which are common to find the cause of Knee pain. This study aim to determine knee MRI appropriateness, in Valiasr hospital of Birjand in 2014.</p><p class="abstract"><strong>Methods:</strong> In this study descriptive – analytical study, 150 patients referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The research results indicated that 56.7%, 39.7%, and 3.6% of the prescriptions were appropriate, inappropriate, and uncertain, respectively. Results from other studies confirmed the inappropriate lumbar and knee MRI prescriptions in Iran . Studies previously conducted in Iran show that the inappropriate lumbar MRI prescriptions varied from 2.6% to 80% and could be attributed to differences in the clinical guidelines used, the prevalence of musculoskeletal disorders, and level of access to MRI centers in different parts of Iran .…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The research results indicated that 56.7%, 39.7%, and 3.6% of the prescriptions were appropriate, inappropriate, and uncertain, respectively. Results from other studies confirmed the inappropriate lumbar and knee MRI prescriptions in Iran . Studies previously conducted in Iran show that the inappropriate lumbar MRI prescriptions varied from 2.6% to 80% and could be attributed to differences in the clinical guidelines used, the prevalence of musculoskeletal disorders, and level of access to MRI centers in different parts of Iran .…”
Section: Discussionmentioning
confidence: 53%
“…This intervention could reduce the ethical hazards and requests made by individuals having supplementary insurance because of the additional cost . It is possible for insurance organizations to reduce their economic burden and that of patients by providing training and departments that supervise physician prescriptions in accordance with clinical guidelines …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations